Hybrid VTOL UAV technologies: Efficiency, customization, and sector-specific applications - Mohammed Osman; Yuanqing Xia; Mohammed Mahdi; Azzam Ahmed (Alexandria Engineering Journal)
The vertical take-off and landing (VTOL) drone is an innovative technology that offers enhanced operational flexibility by combining vertical take-off and landing capabilities with efficient forward flight, eliminating the need for runways. This review provides a comprehensive analysis of hybrid VTOL systems, focusing on their application-specific customization, efficiency improvements, and operational benefits. Special attention is given to the unique capabilities of tilt-rotor, tilt-wing, and dual systems for various sectors, including agriculture, surveying, and cargo transportation. By comparing current market offerings, this work aims to guide engineers and decision-makers in selecting optimal UAS platforms. Furthermore, recent advances in autonomous functions, material innovation, and 3D printing applications are also explored.